Women's issues in Margaret Atwood's The handmaid's tale [ - Nelson, David E. (Gale virtual reference library, 2012)
Examines Margaret Atwood's life, explores from various angles how Atwood addresses women's issues in The Handmaid's Tale, and considers ongoing issues facing women in the twenty-first century